Penentuan Tingkat Resiko Gempabumi Berdasarkan Peak Ground Acceleration (PGA) di Daerah Istimewa Yogyakarta - Kusmita, Tri; Octavia, Yoanda; Mardiyanto (Jurnal Riset Fisika Indonesia, 2024)
Special Region of Yogyakarta is an areas with highest probability of earthquakes. This is caused by the movement of the Indo-Australian plate in the southern Java and the movement of local faults spread across in other area. Therefore, the Special Region of Yogyakarta is interesting to study. This study aims to determine intensity and Peak Ground Acceleration (PGA) value and then describe the potetntial impact due to future earthquakes.. Earthquake data was obtained from a database catalog of earthquake events recorded at the BMKG Geophysics Station Class I Sleman at years 2005-2015. The method used to determine the PGA is Gutenberg-Richter. The results in this study, PGA was applied by Gutenberg-Richter (PGA) value with the Gutenberg-Ritchter method has a value highest 147 gal (VII-IX MMI). The area with the potetntial impact due to future earthquake is Bantul regency.